The limits of intelligent personal assistants. (19th March 2015) - DALE, ROBERT
Abstract: In almost every science fiction movie you'll see people conversing with machines. Of course, the rise of intelligent personal assistants means you probably do this yourself already. This posting asks: what's the difference? Also, recent news on Facebook acquisitions, spoken language translation, and sentiment analysis.